If f (x) = x + 7, g(x) = 2x - 5, and h(x) = 2x + 4, then what is f(x) + h(x)*g(x) - 12?

### 1 Answer | Add Yours

`f(x) = x+7`

`g(x) = 2x-5`

`h(x) = 2x+4`

What you have asked is just the simple arithmetic involved with functions.

`f(x) + h(x) xx g(x) - 12`

`= (x+7)+(2x+4)xx(2x-5) - 12`

`=x+7 + (4x^2-10x+8x-20)-12`

`= x+7 + 4x^2-2x-20-12`

`= 4x^2-x -25`

Therefore,

`f(x) + h(x) xx g(x) - 12 = 4x^2-x -25`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes